Panorama of Maternal Mortality in Brazil for Direct Obstetric Causes (Research, Society and Development, 2022)
The maternal mortality is considered a global health problem and can be classified in two ways: indirect and direct causes. Both occur in the pregnancy-puerperal period. In addition, the objective of this study was to evaluate the panorama of maternal mortality due to direct obstetric causes in Brazil, during the last five years. It is an ecological study, with a descriptive objective and quantitative approach. The data collection took place through the Informatics Department of the Brazilian Unified Health System (DATASUS) during the period between March and April 2021, through the analysis of the following variables: deaths occurred in women between 10 and 49 years old, in the period of pregnancy, at the time of delivery or in the puerperium, related to abortion, hypertensive disorder, hemorrhage and puerperal infection, in the period between 2016 and 2020. The maternal deaths that happened in Brazil, most of them are due to direct obstetric causes. On the Southeast and Northeast had the highest rates, the first being more prevalent among abortion, hemorrhage and puerperal infection and the second among hypertensive disorders. Observed a decline in the number of maternal mortality rate due to direct obstetric causes during in the studied years, through adherence to the projects presented by the Ministry of Health. It is necessary to implement new strategies and raise mothers' awareness about the gestational and puerperal period.